Single-atom-layer traps in a solid electrolyte for lithium batteries - Feng Zhu (Nature Portfolio, 2020)
High ionic conductivity in solid electrolytes is dependent on the existence of features that interrupt the periodic nature of host materials. Here, the authors enrich the defect chemistry in a typical Li-ion conductor, reporting atom-thick planar defects that form closed loops and trap mobile species.